Efeito do aumento da dificuldade da tarefa de colocar o pé no degrau na coordenação intra-membro de pessoas com hemiparesia pós Acidente Vascular Cerebral - Marques, Fabiana Silva (Universidade Federal de São Carlos, 2025)
Stroke (Cerebrovascular Accident) can result in motor sequelae, such as hemiparesis, which affect individuals' mobility and quality of life. Performing complex functional tasks—such as stepping up onto a stair—requires coordination, strength, and postural control, and can be individually challenging depending on the degree of motor impairment. In this context, the way these tasks are structured and practiced during rehabilitation directly influences adjustments in motor behavior. Although task-oriented practice is an effective approach in neurological rehabilitation, there is still a lack of evidence on the effects of systematically progressing task difficulty, as well as on the most appropriate criteria for individualization based on each patient's functional characteristics. Objectives: The first objective was to investigate the effects of progressing the difficulty of a functional task—placing the paretic lower limb on a step—on intra-limb coordination in post-stroke individuals. The second study aimed to identify the anthropometric and functional factors that influence the choice of step height. Materials and Methods: This study included 24 chronic post-stroke individuals, average age 60.96 years, divided into two groups: Group 1 (step height progression) and Group 2 (no changes in height). The functional exercise consisted of placing the affected limb on a step, repeating the movement 10 times per set, for a total of 10 sets, with height adjusted based on the Rating of Perceived Challenge (RPC) scale. Biomechanical data were captured using the Qualisys system and processed with Visual 3D and MATLAB software, focusing on hip, knee, and ankle joint angles in the sagittal plane. Statistical analysis used Statistical Parametric Mapping (SPM), allowing for the evaluation of changes throughout the time series. The second study included 29 chronic post-stroke individuals aged 42 to 82 years, with hemiparesis for ≥6 months, able to walk ≥8 meters three times a day, and meeting the adjusted cut-off points of the Mini-Mental State Examination (MMSE). Step height selected by participants was measured using the Rating of Perceived Challenge (RPC) scale, based on the ideal range (6–8). Other parameters analyzed included lower limb length, motor recovery (Fugl-Meyer Assessment), and functional mobility (Timed Up and Go, TUG). Analyses included Pearson correlations between variables and a multiple linear regression model to determine the relative contribution of each variable to the height selection. Results: The first study's results showed that progressing the step height significantly influenced hip and knee joint angles, especially during the ascent and descent phases in the progression group, suggesting motor adjustments in response to increased difficulty. The ankle maintained stable patterns, indicating less adaptation to the challenge. Variability analysis (standard deviation) did not show significant changes, suggesting consolidated motor patterns even under progression. In the second study, chosen step height positively correlated with lower limb length (r = 0.48) and Fugl-Meyer scores (r = 0.66), and negatively with TUG time (r = -0.54). The regression model indicated that lower limb length and TUG time explained 50.4% of the variance in step height selection, with TUG being a more robust predictor after statistical control. Conclusion: Progressing functional tasks can promote important motor adaptations in the hip and knee of post-stroke individuals, while repetition supports the stabilization of motor patterns. Additionally, selecting step height should consider anthropometric measurements and functional performance, reinforcing the importance of personalized approaches in rehabilitation.
Effect of increased task difficulty of foot placement on the step on intra-limb coordination in individuals with post-stroke hemiparesis
Keywords: Acidente Vascular Cerebral; Progressão de tarefa; Coordenação motora; Reabilitação funcional; Variabilidade motora; Terapia de contensão induzida; Hemiparesia; Terapia orientada a tarefa; Altura do degrau; Motor variability; Stroke; Task progression; Motor coordination; Functional rehabilitation; Constraint-induced therapy; Task-oriented therapy; Hemiparesis; Step height; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL